Gender, livestock and livelihood indicators. Version 2 - Njuki, Jemimah; Poole, Elizabeth J.; Johnson, Nancy L.; Baltenweck, Isabelle; Pali, Pamela N.; Lokman, Z.; Mburu, S. (International Livestock Research Institute, 2011)
This guide is a reference point for some of the important indicators that ILRI can use to monitor the changing role of livestock in livelihoods in different production systems and the impact of livestock-related interventions. While this list of indicators is not comprehensive in covering all the areas in which ILRI works, it provides a starting point for the common objectives which most of our projects, be they in markets, biotechnology or the environment, hope to achieve. Some of these indicators are already commonly used in different surveys but their application has not always been consistent or comparable. With time, we expect to develop further common indicators around other areas of research in ILRI. This document should therefore be considered as a living document to which we will add core indicators around the thematic areas covered by ILRI’s research including such areas as partnerships, capacity building and the key thematic areas of markets, biotechnology and environment. This document should be used to guide your data collection within projects. These may include baseline data, evaluation (both internal and external), impact assessments, project appraisals and any other data collection within the projects and programs across the institute, including surveys conducted by students where possible. Currently, the indicators are designed for data collection at household level and for integration into household surveys. Project teams should ask for assistance in adapting these indicators for use in other types of surveys such as community surveys, focus group discussions, market agent surveys and key informant interviews. Livestock play multiple roles in livelihoods. In deriving these indicators, we have used both the sustainable livelihoods framework, placing livestock within an assets and capital framework, and as a pathway out of poverty. The latter recognizes that for livestock to translate into poverty reduction the necessary conditions i.e. technologies and services to generate productive, sustainable and profitable markets are a pre-requisite